1971
DOI: 10.1515/zna-1971-0211
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Diffuse Reflectance Spectra of V2O5 Powder

Abstract: On the base of Schuster-Kubelka-Munk's theory, quantitative relations between the bulk absorp­ tion and diffuse reflectance spectra of undiluted and diluted semiconductor powder samples are established in the region of the long-wave tail of the absorption edge. Investigations in the long­ wave region of the diffuse reflectance spectra of V

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(18 citation statements)
references
References 0 publications
4
14
0
Order By: Relevance
“…The edge energy, or in other words the band-gap energy of V 2 O 5 crystallites, is 2.3 eV in this work, in good agreement with the literature value of 2.3-2.4 eV. [40][41][42] From the results in Table 4, it is concluded that three major factors affect the edge energy of the V(V) cations, as discussed below:…”
Section: Bulk Compositions Andsupporting
confidence: 90%
“…The edge energy, or in other words the band-gap energy of V 2 O 5 crystallites, is 2.3 eV in this work, in good agreement with the literature value of 2.3-2.4 eV. [40][41][42] From the results in Table 4, it is concluded that three major factors affect the edge energy of the V(V) cations, as discussed below:…”
Section: Bulk Compositions Andsupporting
confidence: 90%
“…Figure 2 B shows plots of the modified Kubelka-Munk function versus the photon energy, from which the band-gap energies can be obtained. [33] The band-gap energy for TiO 2ÀX N X can be seen to be 2.95 eV, corresponding to the visible-light region, whereas that for undoped TiO 2 is 3.2 eV.…”
Section: Resultsmentioning
confidence: 96%
“…Diffuse reflectance spectra were measured relative to corundum (Hoechst Ceram Tec) with a Shimadzu Model 3101 spectrophotometer equipped with an integrating sphere unit. The onset of the lowest energy transition E on was determined according to the method by Karvaly and Hevesi [60] as described previously. [2a] Cyclic voltammetry was performed with an EG&G Princeton Applied Research Model 264A potentiostat by using a conventional three-electrode assembly consisting of a glassy-carbon working electrode, a platinum wire as counter electrode, and an Ag/AgCl reference electrode in saturated KCl solution.…”
Section: Methodsmentioning
confidence: 99%